Nerve Imaging in the Wrist - Daniels, Steven P.; De Tolla, Jadie E.; Azad, Ali; Petchprapa, Catherine N. (Seminars in Musculoskeletal Radiology, 2022)
Neuropathic symptoms involving the wrist are a common clinical presentation that can be due to a variety of causes. Imaging plays a key role in differentiating distal nerve lesions in the wrist from more proximal nerve abnormalities such as a cervical radiculopathy or brachial plexopathy. Imaging complements electrodiagnostic testing by helping define the specific lesion site and by providing anatomical information to guide surgical planning. This article reviews nerve anatomy, normal and abnormal findings on ultrasonography and magnetic resonance imaging, and common and uncommon causes of neuropathy.
Keywords: wrist; magnetic resonance imaging; ultrasonography; peripheral nerves; carpal tunnel syndrome